Kontrol Diri Anak Asuh di Lembaga Kesejahteraan Sosial Anak (LKSA) Muhammadiyah Cabang Sumur Bandung Kota Bandung - Devy Yuanita Savitry; Ramli Rahman; Nurrohmi Nurrohmi (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2023)
Self-control refers to a simple psychological component that includes the individual's ability to modify behavior, manage unwanted information by interpreting it, and take actions based on what they believe. This study aimed to obtain an overview regarding the self-control of foster children in the Muhammadiyah Children Welfare Institution (LKSA) Sumur Bandung in Bandung City which can be seen from the informant's characteristics, behavioral control, cognitive control, and decision control. This study used descriptive qualitative method. The determination of informants in this study was carried out using a purposive sampling technique, namely six informants consisting of three foster children and three LKSA caretakers. The data collection techniques used were in-depth interviews and documentation studies. The validity of the data test was carried out by conducting four tests, namely credibility (internal validity), dependability (dependence), transferability (transferability), and confirmability (certainty). The data analysis technique used were data reduction, data presentation, verification, and withdrawal of research results. The results showed the characteristic data of the six informants and that foster children at the Muhammadiyah LKSA Sumur Bandung in Bandung City are not be able to do self-control yet. The behavioral control consists of two components, namely the ability to regulate implementation and modify stimulus. The cognitive control consists of two components, namely the ability to obtain information and make judgments. The decision control consists of two components, namely confidence in the decisions taken and readiness to accept the consequences. The problems found were the foster children at the Muhammadiyah LKSA Sumur Bandung in Bandung City were not being able to control the situation, being closed-off in gaining information, not being able to make an assessment, and being unready to make a decision. In order to solve those problems, the researcher proposed a program entitled "Group Counseling for Increasing Self-Control of Foster Children at Muhammadiyah LKSA Sumur Bandung in Bandung City".